2019
DOI: 10.3122/jabfm.2019.06.190092
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Inflammatory Index Is Associated With Diabetes Severity

Abstract: The Dietary Inflammatory Index (DII) is a recently developed dietary inflammation assessment tool. The current study examined the association between DII and the presence and severity of diabetes in adults age >20 years. Research Design and Methods: Cross-sectional analysis of 4434 adult participants in the National Health and Nutrition Examination Survey (NHANES 2013 to 2014). The DII was calculated based on 24hour dietary recall data. Linear and logistic regression models were used to estimate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
(11 reference statements)
1
25
0
Order By: Relevance
“…Denova-Gutiérrez et al (22) reported having a higher risk of diabetes in participants with high DII scores (who consume a more pro-inflammatory diet) than in those with low DII scores (who consume a more antiinflammatory diet). In another study that investigated DII and diabetes risk, it was shown that the risk of diabetes increased by 13 % with every 1-point increase in DII score (17). The findings of the present study are in line with these studies, and it was found that the risk of diabetes also became higher as the DII scores of individuals increased.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Denova-Gutiérrez et al (22) reported having a higher risk of diabetes in participants with high DII scores (who consume a more pro-inflammatory diet) than in those with low DII scores (who consume a more antiinflammatory diet). In another study that investigated DII and diabetes risk, it was shown that the risk of diabetes increased by 13 % with every 1-point increase in DII score (17). The findings of the present study are in line with these studies, and it was found that the risk of diabetes also became higher as the DII scores of individuals increased.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the index, a higher DII score represents a pro-inflammatory diet, whereas a lower score represents an anti-inflammatory diet (16). Besides, only a few studies have investigated the relationship between the inflammatory potential of diet as measured by DII and T2DM (14,17). To the best of our knowledge, no studies have focused on the mediator role of fetuin-A in this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…After further assessment by reading the full texts, a further six articles were excluded because they did not utilize the DII (one study), had incomplete data (one study), did not include an accurate definition of DM (two studies), or were irrelevant (one study). Five studies ultimately met the inclusion criteria and were merged to evaluate associations between the two extreme categories of the DII score and risk of DM (13)(14)(15)(16)(17). The flow of the above-described procedures is shown in Figure 1.…”
Section: Literature Researchmentioning
confidence: 99%
“…The relationship between the DII score and DM is controversial. Some studies suggest a positive relationship between the DII score and DM (13)(14)(15), whereas other studies indicate no positive association (16,17) or a negative association (18). To date, only one narrative review by Phillips et al has assessed the relationships between DII and DM (19), but no systematic review and meta-analysis has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a wonderful family medicine article using the National Health and Nutrition Examination Survey (NHANES) dietary recall data confirms what many have suspected. King et al 4 document that diabetes is associated with a diet high in foods associated with postmeal increases in 6 established inflammatory biomarkers (IL-1␤, IL-4, 58 IL-6, IL-10, TNF-a, and C-reactive protein). Think sugars, transfat, refined carbohydrates, excess alcohol, and processed meat.…”
Section: Improving Clinical Care: Inflammatory Diet and Diabetes Andmentioning
confidence: 99%